Mechanistic and psychological explanations of behaviour: the problem of mental causation - Davies, Ronald Gavin (Department of Philosophy, 2023)
The problem we are going to investigate is that of mental causation. Human beings often explain to each other why they do what they do by citing their reasons, that is, mental states like beliefs and desires. Explanations of behaviour which invoke mental causes are known as psychological explanations. Mechanistic explanations, on the other hand, make sole reference to the neurophysical going-on in our bodies causally to explain behaviour. This kind of explanation has become entrenched in a naturalistic attitude towards any phenomemon which requires causal explanation. This naturalistic attitude, furthermore, holds explanation by reference to natural causal law in especially high esteem. Our problem is going to be how, given the availability of mechanistic explanation, psychological explanations can still apply. That is, given the availability of explanation of human behaviour, by reference to physical (or neurophysiological) laws, can mental states still constitute causes of behaviour This problem has become very well defined since a series of papers authored by Donald Davidson who showed, very clearly, how the problem arises given the following three principles : (i) the Principle of Causal Interaction which holds that mental states interact causally with physical states. (2) the Principle of the Nomological Character of Causality which states that events related as cause and effect fall under strict laws and (3) the Principle of the Anomalism of the Mental which states that there are no strict laws, known or unknown, on the basis of which the mental can be predicted and explained. A central feature of Davidson s philosophy is (3) and one of the most significant sections of this thesis will concern why Davidson formulates (3) as a principle. We need to understand Davidson s arguments for (3) if we are to gain a proper understanding of how he derives the token-identity thesis from (I), (2) and (3). This is important for our purpose here since the latter part of this essay will be an examination of the token-identity thesis as a proposed solution to the problem of mental causation.